(6n+3)5+2(3+5+N)=

Simple and best practice solution for (6n+3)5+2(3+5+N)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6n+3)5+2(3+5+N)= equation:


Simplifying
(6n + 3) * 5 + 2(3 + 5 + N) = 0

Reorder the terms:
(3 + 6n) * 5 + 2(3 + 5 + N) = 0

Reorder the terms for easier multiplication:
5(3 + 6n) + 2(3 + 5 + N) = 0
(3 * 5 + 6n * 5) + 2(3 + 5 + N) = 0
(15 + 30n) + 2(3 + 5 + N) = 0

Combine like terms: 3 + 5 = 8
15 + 30n + 2(8 + N) = 0
15 + 30n + (8 * 2 + N * 2) = 0
15 + 30n + (16 + 2N) = 0

Reorder the terms:
15 + 16 + 2N + 30n = 0

Combine like terms: 15 + 16 = 31
31 + 2N + 30n = 0

Solving
31 + 2N + 30n = 0

Solving for variable 'N'.

Move all terms containing N to the left, all other terms to the right.

Add '-31' to each side of the equation.
31 + 2N + -31 + 30n = 0 + -31

Reorder the terms:
31 + -31 + 2N + 30n = 0 + -31

Combine like terms: 31 + -31 = 0
0 + 2N + 30n = 0 + -31
2N + 30n = 0 + -31

Combine like terms: 0 + -31 = -31
2N + 30n = -31

Add '-30n' to each side of the equation.
2N + 30n + -30n = -31 + -30n

Combine like terms: 30n + -30n = 0
2N + 0 = -31 + -30n
2N = -31 + -30n

Divide each side by '2'.
N = -15.5 + -15n

Simplifying
N = -15.5 + -15n

You can always share this solution

See similar equations:

| 3/6(m-4/2)=1 | | 3x-6y=-3 | | p-6(2p-4)=4p+9 | | x+7=2x-13cm | | x=9x-24 | | 2n-1.6=5.2 | | 6n+4=8n-16 | | x^4=11x^2-18 | | 9=4n-(8n+1) | | 7n-2n+10=3n-16 | | 5y-9=-14+(-14) | | -5y+2=-2(4y+11) | | 6(3+-0.6y)-10y=30 | | 1/5+5=13 | | 18=-6(x+5) | | 2X+1X-59=10 | | d/0.5=11 | | 30000x=45000x-275000 | | -12+29=-4h-17 | | 6(x+9)=15 | | 2y-10+5(-2+0.8y)+4y=180 | | x=4z+y | | 14w-21+5w=51 | | 14+4=X | | 1x-81-21x=-1 | | 31=-9z+24 | | 6x^2+9x+21=0 | | 6x^2-9x-21=0 | | x=8x+14 | | -12y+-40=7y-2 | | 2n^2+8n-42=0 | | 7x-5+3x+15=5x+4y | | -7+8=11 | | 21+(-3)= | | 3x(7x-4)+6x-(13-24x^2)= | | 8x(9)x(2)x(-1)= | | 6x+12=2x-6 | | 14/3b+4/5=15/7b-1/5b-1/3 | | 7x-5+3x+15=5x+4 | | 4/5x=4 | | x=4x+9 | | 37/7m-9/10=4/5m | | -9n+8=-21n | | x^3-8x^2+16x-128=0 | | 36x(-4)= | | 5/2/7m-9/10=4/5m | | K^2+6k-16=0 | | (-48)/2/19 | | 52/7m-9/10=4/5m | | X/7=28 | | 6d-9=1d+1 | | 567+(-100)= | | 2(3.6+-0.2y)-y=3 | | -48/2/19 | | 5x^2+40x+80=o | | 9k-4=14 | | 3/4+1/4=7/8*r+3/8*r | | (3y+1)*27= | | 35x(-3)= | | 14x+2= | | -3/4+1/4=-7/8*r+3/8*r | | 7x+15=17x-6 | | 2x=8x-12 | | -5(2)+2n= | | 15x-4=7-12x |

Equations solver categories